Deep mantle structure and origin of Cenozoic intraplate volcanoes in Indochina, Hainan and South China Sea - Zhao, Dapeng; Toyokuni, Genti; Kurata, Kenkichi (Geophysical journal international, 2021)
SUMMARY Cenozoic basalts with ages ranging from 28.5 to < 0.1 Ma are widely distributed in the Indochina block, the South China Sea basin and the Leiqiong area in South China including the Leizhou Peninsula and the northern Hainan Island, which form the southeastern Asian basalt province (SABP). These Cenozoic basalts share common petrological and geochemical characteristics. However, the origin of the Cenozoic intraplate volcanism in the SABP is still a controversial issue. In this work, we apply a novel technique of multiscale global tomography to study the whole-mantle 3-D P-wave velocity (Vp) structure beneath the SABP. Our results show that low-Vp anomalies prevail in the whole mantle beneath the SABP. Although the strongest low-Vp zones exist beneath Hainan, significant low-Vp anomalies are also visible in the mantle beneath other parts of the SABP. These low-Vp anomalies appear somehow independent, rather than deriving from a single plume. We deem that a cluster of plumes rather than a single plume existed in the Cenozoic and may still exist now in the mantle beneath the SABP, though the Hainan plume may be the strongest one. A geochemical study suggested that the Hainan plume upwelling might be slowing down and close to exhausting its source zone. This geochemical inference is supported by our tomographic images showing that the low-Vp zones under Hainan are weak and intermittent in the lower mantle (∼700–2889 km depths). The low-Vp zones in the mantle beneath other SABP Cenozoic volcanoes are also weak, suggesting that those mantle plumes, if any, are also dying or already dead. As compared with a strong single plume, each member in a plume cluster should be small and weak, and so hard to exist long. The SABP is surrounded by subduction zones. The hot mantle upwelling beneath the SABP might be caused by collapsing of subducted slabs down to the lowermost mantle.